Implication of corporate social responsibility and legislations on reverse logistics practices : implementation decisions and performance appraisal - Lu, Jiaxin (2017)
Despite challenges and barriers, there are various drivers, internal and external, that advocate the implementation of RL. Corporate social responsibility (CSR) and government legislations are some of the emerging paramount drivers. This paper investigates how these drivers influence decision making in whether and how to implement RL, and how the performance of an RL system is assessed in a balanced manner. Considerations on CSR are having an impact on RL network design in many ways, such as location and size of facilities, outsourcing RL to a third party, and application of technology. Upon its implementation, the performance assessment of an RL system should incorporate environmental and social dimensions apart from economic. Existing approaches including GreenSCOR, triple bottom line (TBL) and sustainable balanced scorecard (SBSC) are discussed, and a new theoretical framework based on the advantages of existing ones is proposed. Current issues and future trends of RL associated with sustainability are highlighted as concluding discussions, such as the development of technology that facilitates forecasting of product returns and adoption of RL for charity and philanthropic purposes.